THE IMPORTANCE OF NON-AGRICULTURAL ECONOMIC ACTIVITY OF FARMERS IN THE MODERNIZATION PROCESS OF FARMS - Ostromęcki, Artur; Mantaj, Andrzej; Zając, Dariusz (Acta Scientiarum Polonorum. Oeconomia, 2015)
The aim of this article is to identify and assess the degree and conditionings of the phenomenon of subsidizing farms from the income obtained by farmers from their non-agricultural economic activity. The empirical material of the article are the results of the survey conducted in 2011-2012, i.e. the questionnaire interview with 210 farmers, owners of individual farms, additionally engaged in non-agricultural economic activity, from the area of south-east Poland, i.e. from three voivodships: Świętokrzyskie, Małopolskie and Podkarpackie. The analysis of the research results shows that the processes associated with running a farm, which are important from the farmers' point of view, are supported financially from the income obtained by them from non-agricultural economic activity, as evidenced by statistically significant and positive parameters of logistic regression of the models presented in the article, in almost all the analyzed cases.